2022
DOI: 10.1039/d2ta00022a
|View full text |Cite
|
Sign up to set email alerts
|

Favorably adjusting the pore characteristics of copper sulfide by template regulation for vapor-phase elemental mercury immobilization

Abstract: Copper sulfide (CuS) is an effective solution to address the ecosystem concern under the restriction of the Minamata Convention and mitigate the intensive elemental mercury (Hg0) pollution worldwide. However, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…On the contrary, pyrrhotite with abundant S – sites had a larger Hg 0 adsorption capacity, which indicated that S – sites exhibited a higher reactivity than S 2– sites for Hg 0 capture . Furthermore, with the assistance of S n 2– sites, the Hg 0 adsorption capacity and uptake rate of CuS could reach 208.5 mg g –1 and 97.3 μg g –1 min –1 , respectively . According to the summarized data in Table , it can be concluded that the Hg 0 adsorption activities of S 2 2– and S n 2– were generally higher than those of S 2– sites.…”
Section: Raw Metal Sulfidesmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, pyrrhotite with abundant S – sites had a larger Hg 0 adsorption capacity, which indicated that S – sites exhibited a higher reactivity than S 2– sites for Hg 0 capture . Furthermore, with the assistance of S n 2– sites, the Hg 0 adsorption capacity and uptake rate of CuS could reach 208.5 mg g –1 and 97.3 μg g –1 min –1 , respectively . According to the summarized data in Table , it can be concluded that the Hg 0 adsorption activities of S 2 2– and S n 2– were generally higher than those of S 2– sites.…”
Section: Raw Metal Sulfidesmentioning
confidence: 95%
“…60 Furthermore, with the assistance of S n 2− sites, the Hg 0 adsorption capacity and uptake rate of CuS could reach 208.5 mg g −1 and 97.3 μg g −1 min −1 , respectively. 62 According to the summarized data in Table 2, it can be concluded that the Hg 0 adsorption activities of S 2 2− and S n 2− were generally higher than those of S 2− sites. In addition, the metal sulfides with plenty of S n 2− sites exhibit better Hg 0 adsorption performance.…”
Section: Raw Metal Sulfidesmentioning
confidence: 99%
“…The surface chemical state of CuS-h120 after Hg 0 removal test was analyzed by XPS. As shown in Figure a, the high-resolution S 2p XPS spectrum of the spent CuS-h120 can be divided into five main peaks located at 161.21, 162.13, 163.27, 164.25, and 168.87 eV, which can be assigned to S 2– , S 2 2– , S x 2– , and SO x 2– species, respectively . After Hg 0 adsorption, the peak position of S x 2– has no obvious change, whereas the ratio of it declines from 38.22 to 28.89%, suggesting that S x 2– species have directly reacted with Hg 0 .…”
Section: Results and Discussionmentioning
confidence: 96%
“…21 , and SO x 2− species, respectively. 44 After Hg 0 adsorption, the peak position of S x 2− has no obvious change, whereas the ratio of it declines from 38.22 to 28.89%, suggesting that S x 2− species have directly reacted with Hg 0 . Meanwhile, the percentage of S 2− increases from 40.57 to 48.13%, and the ratio of S 2 2− rises from 21.21 to 22.98%.…”
Section: Environmentalmentioning
confidence: 91%
“…HCl rather than Cl 2 accounted for the oxidation of Hg 0 on the CuO(111) surface. In 2017, He et al 68 studied the Hg 0 adsorption behaviors on transition metal-doped CuO (110) surface. Only the Zn-doped CuO(110) surface had a higher binding energy than the undoped CuO (110) surface.…”
Section: Copper Oxide (Cuo)mentioning
confidence: 99%